2009
DOI: 10.21608/asat.2009.23484
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical Behavior for a Selected Rubber- Modified Epoxy Adhesive

Abstract: Epoxy resin based on diglycidyl ether of bisphenol A and varying content of hydroxyl terminated polybutadiene (HTPB) were cured using a polyamide curing agent. The ultimate aim of the study was to modify the epoxy matrix by liquid rubber so as to improve its toughness. Tensile, flexural, and impact properties were evaluated. The morphological evolution of the toughened networks was examined by scanning electron microscope, and the observations were used effectively to explain the obtained impact properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Epoxy thermoset resins attracted significant interest because of their excellent properties and found various applications. , Epoxy thermosets, because of their inherent brittle nature and fast crack propagation rate, show poor fracture toughness and fatigue performance which limit their use in industrial applications. One of the efficient ways to overcome this problem and to improve the impact strength of brittle epoxy is the blending with liquid rubbers, especially with carboxyl-terminated poly­(butadiene- co -acrylonitrile) (CTBN). It has been reported that through the inclusion of carboxyl-terminated CTBN rubber, the impact strength of epoxy increases significantly, but a drop in tensile strength and thermal property are also recorded. The addition of a rigid nanofiller along with carboxyl-terminated CTBN can compensate the loss in stiffness without reducing toughness of the epoxy thermoset.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy thermoset resins attracted significant interest because of their excellent properties and found various applications. , Epoxy thermosets, because of their inherent brittle nature and fast crack propagation rate, show poor fracture toughness and fatigue performance which limit their use in industrial applications. One of the efficient ways to overcome this problem and to improve the impact strength of brittle epoxy is the blending with liquid rubbers, especially with carboxyl-terminated poly­(butadiene- co -acrylonitrile) (CTBN). It has been reported that through the inclusion of carboxyl-terminated CTBN rubber, the impact strength of epoxy increases significantly, but a drop in tensile strength and thermal property are also recorded. The addition of a rigid nanofiller along with carboxyl-terminated CTBN can compensate the loss in stiffness without reducing toughness of the epoxy thermoset.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins based on diglycidyl ether of bisphenol A and varying content of hydroxyl terminated polybutadiene (HTPB) were cured using a polyamide curing agent to modify the epoxy matrix by liquid rubber to improve its toughness. 7 Different mechanical properties were evaluated. The morphological evolution of the toughened networks was examined by scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%